Gender Disparity in Editorial Boards of Lithuanian Scientific Journals: An Overview of Different Science Disciplines - Šuminas, Andrius (Septentrio Conference Series, 2023)
Editors-in-chief and members of editorial boards of scientific journals play an extremely important role in the development of science and assure research integrity, as scientific publications are the major results of research. While gender parity in tenure-track hiring decisions and promotion rates has improved, female academics remain underrepresented in senior career phases, including editors-in-chief and members of editorial boards positions of scientific journals. Journal editors and members of editorial boards exert considerable power over what is published and in certain cases the direction of an academic discipline and the career advancement of authors. For this reason it is important to minimize biases extrinsic to the merit of the work impacting publication decisions. One way to achieve this is to ensure a diverse pool of editors and members of editorial boards, ensuring the widest possible coverage of different competencies. This is in line with a diversity model of editorial appointment where editorial boards are structured to dismantle wider conditions of inequality. Another possible option, a distributive model would seek an editorial board reflective of existing proportions in the field at large. The poster presents comprehensive results of a study of Lithuanian scientific journals. During the research process publicly available information from all scientific journals published in Lithuania was reviewed, to infer the proportions of members of editorial boards by gender. The results of the study revealed differences the proportions of male and female members of editorial boards in different disciplines of science.